Effect of Preheating on the Physical Properties of Bis-GMA-Containing, Bis-GMA-Free and Glass Ionomer-Based Fissure Sealants - Yilmaz, Burcu (2026)
This study aimed to evaluate in vitro the effects of preheating on the microhardness and surface roughness of fissure sealants with different compositions. Resin-based sealants (Clinpro, Fissurit FX), Bis-GMA-free resin-based sealants (Helioseal F Plus), and glass ionomer-based sealants (Riva Protect) were tested. Fifty-six cylindrical specimens (n=7) were prepared at room temperature and at 55 ± 1°C. Preheating was performed using Ena Heat. Microhardness was measured with a Vickers tester, and surface roughness was evaluated using an atomic force microscope. Data were analyzed using one-way ANOVA, Tukey’s post hoc, and t-tests. Preheating significantly increased microhardness in all groups (p<0.05). Surface roughness decreased in Helioseal F Plus and Fissurit FX (p<0.05) but remained unchanged in Clinpro and Riva Protect (p>0.05). These results indicate that preheating enhances the microhardness of all fissure sealants, while its effect on surface roughness depends on the material type.